2006
DOI: 10.3102/01623737028003259
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Merit-Based Student Grant Programs: An Event History Analysis

Abstract: As of 2005, 15 states had adopted a broad-based merit aid program, providing a combined $1.2 billion for college students on the basis of academic qualifications. This represents a shift away from a long tradition of need-based aid at the state and federal levels. This article utilizes a Cox proportional hazards model to analyze states’ characteristics that are associated with their probability of adopting a merit aid program. Lower levels of college continuation and educational attainment are found to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 57 publications
4
103
0
1
Order By: Relevance
“…John et al draw attention to the time-varying nature of explanatory factors of student persistence, noting that "changes over time in financial aid packages can influence students' academic and social integration processes, as well as their subsequent persistence decisions" (St. John et al, 2000a, p. 41). To address this need education scholars have begun applying event history analysis techniques developed in other fields to the study of persistence (Chen, 2008;DesJardins et al, 1994DesJardins et al, , 2002aDesJardins et al, , b, 2003Doyle, 2006).…”
Section: The Limited Time Perspective Of Aid Effects and Student Persmentioning
confidence: 99%
“…John et al draw attention to the time-varying nature of explanatory factors of student persistence, noting that "changes over time in financial aid packages can influence students' academic and social integration processes, as well as their subsequent persistence decisions" (St. John et al, 2000a, p. 41). To address this need education scholars have begun applying event history analysis techniques developed in other fields to the study of persistence (Chen, 2008;DesJardins et al, 1994DesJardins et al, , 2002aDesJardins et al, , b, 2003Doyle, 2006).…”
Section: The Limited Time Perspective Of Aid Effects and Student Persmentioning
confidence: 99%
“…Researchers and news sources in education (e.g., Chronicle of Higher Education) also have identified the growing activist role that governors play in PK-12 and postsecondary education (Doyle, 2006;Heller, 2002;Henig, 2009;Johnson & Clark, 2003;McLendon, Heller & Young, 2005;Mokher, 2010;Richardson, Bracco, Callan & Finney, 1999;Selingo, 2001). McLendon, Heller and Young acknowledged that "governors may be performing the 'policy entrepreneur' role that research in other domains has shown is necessary for large-scale policy change to occur" (p. 372).…”
Section: The Role Of Public Entrepreneurs In the Diffusion Of Innovatmentioning
confidence: 99%
“…EHA has been utilized in political science and related fields (i.e., policy studies and public administration) to study a range of policies and programs, including the spread of state lotteries and tax reform (Berry & Berry, 1990, school choice, and other educational reforms (Mintrom, 1997;Mintrom & Vergari, 1998), dual enrollment policies (Mokher & McLendon, 2009), medical savings accounts (Karch, 2006), and e-government approaches to public administration (Jun & Weare, 2011). Most relevant to this study, Doyle (2006) examined the spread of merit aid across US states. His event history analysis indicated that, "no relationship was found between the number of states within a region adopting a program and the likelihood of policy adoption in a given state" (p. 277).…”
Section: Innovation Diffusion Research In Public Policymakingmentioning
confidence: 99%
See 2 more Smart Citations